Impact of Wind Power Generation on a Large Scale Power System Using Stochastic Linear Stability - Becker-Cares, C; Verdejo-Fredes, H; Awerkin, A (Elsevier Inc., 2016)
The effect of random and sustained disturbances is studied in this paper. The Ornstein–Uhlenbeck stochastic process is proposed with the aim to represent the variations in the power output produced by wind power generation, considering measurements of a wind farm located in the fourth region of Chile as real field data for its parameters calibration. An example is provided considering the study of the exponential stability using the Lyapunov exponent as an indicator, with the aim to determine the maximum size of a wind farm that can be connected in a busbar of one of Chile s interconnected power system (Sistema Interconectado del Norte Grande, SING), considering successive increments from the output power from the connected wind farm. © 2016